The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/jb.00129-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Ends and Target Site of a Novel Tetracycline Resistance-Encoding Conjugative Transposon from Enterococcus faecium 664.1H1

Abstract: Enterococcus faecium 664.1H1 is multiply antibiotic resistant and mercury resistant. In this study, the genetic support for the tetracycline resistance of E. faecium 664.1H1 was characterized. The tet(S) gene is responsible for tetracycline resistance, and this gene is located on the chromosome of E. faecium 664.1H1, on a novel conjugative transposon. The element is transferable to Enterococcus faecalis, where it integrates into a specific site. The element was designated EfcTn1. The integrase of EfcTn1 is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…The tet(S) gene has been found among Firmicutes and gammaproteobacteria from diverse ecological sources since the early 1950s (1, 2, 10, 11) (http://faculty.washington.edu/marilynr/tetweb2.pdf), and several genetic platforms carrying tet(S), such as CTn6000, CTn916S, pKL0018, and pK214, have been described (5,9,11). Among enterococci, the genetic context of tet(S) has been characterized in only a single Enterococcus casseliflavus isolate from animal origin (5,15). In this work, we described the genetic platforms of 13 tet(S)-carrying enterococci from different origins and geographical areas and compared them with sequences available in GenBank databases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The tet(S) gene has been found among Firmicutes and gammaproteobacteria from diverse ecological sources since the early 1950s (1, 2, 10, 11) (http://faculty.washington.edu/marilynr/tetweb2.pdf), and several genetic platforms carrying tet(S), such as CTn6000, CTn916S, pKL0018, and pK214, have been described (5,9,11). Among enterococci, the genetic context of tet(S) has been characterized in only a single Enterococcus casseliflavus isolate from animal origin (5,15). In this work, we described the genetic platforms of 13 tet(S)-carrying enterococci from different origins and geographical areas and compared them with sequences available in GenBank databases.…”
mentioning
confidence: 99%
“…Conversely, variants A and B were not detected in the GenBank databases. The analysis of the chromosomal integration sites of CTn6000 variants was performed as described previously (15) and revealed that types B and C use the gene coding for the L31 ribosomal protein as the hot spot for integration, as reported for the original CTn6000 type A (15). However, the L31-encoding gene was not the integration site for type D.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an oriT consensus sequence upstream of ORF16 further supports the rolling circle replication type of plasmid similar to what has been observed for many transferable plasmids in gram-positive bacteria (3). ermB1 is located next to an MLS leader peptide, which is known to regulate erm gene expression in the absence of EM (8), in the first 20-kb region, while the ermB2 gene is located in the plasmid's second 12-kb region downstream of the tetracycline resistance gene tetS. The fact that both of the ermB genes of pKL0018 are identical to that of pRE25 suggests that both genes were originally part of the pKL0018 plasmid.…”
mentioning
confidence: 84%
“…In particular, the emergence of vancomycin-resistant enterococci (VRE) and their potential involvement in the dissemination of resistance-encoding traits to other pathogens, such as Staphylococcus spp., have become a major public health concern (7,51). To date, various resistance traits (conferring resistance to glycopeptides, aminoglycosides, quinupristin-dalfopristin, tetracycline, chloramphenicol, erythromycin, ␤-lactams, and others) have been identified in enterococci, and many are encoded by mobile elements, such as plasmids (33,42,45,46), transposons (17,(36)(37)(38)44), and integrons (4).…”
mentioning
confidence: 99%